Comparison of the effects of a truncating and a missense MYBPC3 mutation on contractile parameters of engineered heart tissue. (August 2016) - Wijnker, Paul J.M.; Friedrich, Felix W.; Dutsch, Alexander; Reischmann, Silke; Eder, Alexandra; Mannhardt, Ingra; Mearini, Giulia; Eschenhagen, Thomas; van der Velden, Jolanda; Carrier, Lucie
Abstract: Hypertrophic cardiomyopathy (HCM) is a cardiac genetic disease characterized by left ventricular hypertrophy, diastolic dysfunction and myocardial disarray. The most frequently mutated gene is MYBPC3, encoding cardiac myosin-binding protein-C (cMyBP-C). We compared the pathomechanisms of a truncating mutation (c.2373_2374insG) and a missense mutation (c.1591G>C) in MYBPC3 in engineered heart tissue (EHT). EHTs enable to study the direct effects of mutants without interference of secondary disease-related changes. EHTs were generated from Mybpc3 -targeted knock-out (KO) and wild-type (WT) mouse cardiac cells. MYBPC3 WT and mutants were expressed in KO EHTs via adeno-associated virus. KO EHTs displayed higher maximal force and sensitivity to external [Ca 2+ ] than WT EHTs. Expression of WT -Mybpc3 at MOI-100 resulted in 73% cMyBP-C level but did not prevent the KO phenotype, whereas MOI-300 resulted in ≥ 95% cMyBP-C level and prevented the KO phenotype. Expression of the truncating or missense mutation (MOI-300) or their combination with WT (MOI-150 each), mimicking the homozygous or heterozygous disease state, respectively, failed to restore force to WT level. Immunofluorescence analysis revealed correct incorporation of WT and missense, but not of truncated cMyBP-C in the sarcomere. In conclusion, this study provides evidence in KO EHTs that i) haploinsufficiency affects EHT contractile function if WT cMyBP-C protein levels are ≤ 73%, ii) missense or truncating mutations, but not WT do not fully restore the disease phenotype and have different pathogenic mechanisms, e.g. sarcomere poisoning for the missense mutation, iii) the direct impact of (newly identified) MYBPC3 gene variants can be evaluated. Highlights: MYBPC3, encoding cardiac myosin-binding protein-C is the most frequently mutated gene in hypertrophic cardiomyopathy (HCM). A truncating and a missense MYBPC3 mutation were expressed in engineered heart tissue (EHT) from Mybpc3 -KO mice. KO EHTs displayed higher maximal force and sensitivity to external [Ca 2+ ] than WT EHTs. Haploinsufficiency affected EHT contractile function if WT cMyBP-C protein levels were ≤ 73%. Missense or truncating mutation, but not WT did not fully restore the disease phenotype and had different pathogenic mechanisms, e.g. sarcomere poisoning for the missense mutation in KO EHTs.